2010
DOI: 10.1183/09031936.00091210
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health in children, and indoor exposure to (1,3)-β-d-glucan, EPS mould components and endotoxin

Abstract: For a long time, exposure to mould and dampness-derived microbial components was considered a risk factor for the development of respiratory diseases and symptoms. Some recent studies suggested that early childhood exposure to mould components, such as (1,3)-b-Dglucan and extracellular polysaccharides (EPSs), may protect children from developing allergy. We investigated the association of exposure to (1,3)-b-D-glucan, EPS and endotoxin with asthma and allergies in 6-yr-old children.This investigation was the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 41 publications
5
48
2
Order By: Relevance
“…However, this could not be confirmed at 3 yrs of age in the same birth cohort [8]. The two European studies did not observe an effect of exposure to (1,3)-b-D-glucan on asthma, wheezing or allergic rhinitis symptoms in school-aged children [9,30].…”
Section: Other Health Outcomesmentioning
confidence: 74%
See 2 more Smart Citations
“…However, this could not be confirmed at 3 yrs of age in the same birth cohort [8]. The two European studies did not observe an effect of exposure to (1,3)-b-D-glucan on asthma, wheezing or allergic rhinitis symptoms in school-aged children [9,30].…”
Section: Other Health Outcomesmentioning
confidence: 74%
“…In one US birth cohort study (the Cincinnati Childhood Allergy and Air Pollution Study) from IOSSIFOVA et al [8], the reported increase in risk was persistent from 1-3 yrs of age. BAKER et al [50] observed no effect of current exposure to visible mould and wheezing at 6 months of age, and TISCHER et al [30] also found no effect in children followed until 6 yrs of age from Germany and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of air pollutants, studies have focused on evaluating concentrations of some pollutants and correlating them with prevalence of respiratory diseases including endotoxin (Liu, 2002;Doreswamy and Peden, 2010). Fewer studies have measured molds and glucans (Bush et al, 2006;Portnoy et al, 2008;Samadi et al, 2009;Tischer et al, 2010). Airborne pyrogens appear to contribute to organic dust toxic syndrome, PhD on fungal and airborne pyrogens as well as problematic test products (dialysis, cytotoxic and lipophilic drugs); joint first author background review on non-endotoxin pyrogens (Hasiwa et al, 2013a) Project manager for the pyrogen test in our group for many years, continues to promote the technology from University of tübingen, Germany Paul-ehrlich-Institute; early evaluation of the test led the eCVAM peer-review and hand-over to ICCVAM Inventor and principal investigator PhD on pyrogen testing of medical devices and removal from surfaces; joint first author background review on non-endotoxin pyrogens (Hasiwa et al, 2013a) Cryoblood validation study partner at Qualis, now Zwisler laboratories, Konstanz, Germany Biometry of the validation studies and modeling of rabbit responses (Hoffmann et al, 2005(Hoffmann et al, , 2006 Kit marketing by Charles-River endosafe (CeO) Partner in validation study at University of Berne, Switzerland Post-doc JHSPH on airborne pyrogens early partner at the Paul-ehrlich-Institute in the development and validation of the test Developed in his PhD the isolation procedure for lipoteichoic acid, the key non-endotoxin pyrogen (Morath et al, 2001) used as reference material in the kits; showed the activity of the respective synthesized structures (Morath et al, 2002;Deininger et al, 2007) and enabled their biological characterization.…”
Section: Emerging Opportunity: Airborne Pyrogensmentioning
confidence: 99%
“…Little is known regarding whether a single bio-contaminant measurement is able to represent the overall exposure within a home, as the microbial components in house dust samples may change over time [30,33]. We chose to focus particularly on early exposure shortly after birth.…”
Section: Discussionmentioning
confidence: 99%